Controlling the drawability of carbon steel wire rod - V. P. Fetisov (Литьë и металлургия)
The author proposed an indicator of the deformation capacity of carbon steel wire rod, which took into account the tendency of the metal to hardening and the general level of plastic properties, and determined technological approaches to the designation of the optimal total reduction before intermediate heat treatment by drawing low carbon wire rod and wire rod for metal cord.